Invertebrate traces in pseudo–coprolites from the upper Cretaceous Marília Formation (Bauru Group), Minas Gerais State, Brazil. (January 2016) - Francischini, Heitor; Paes Neto, Voltaire D.; Martinelli, Agustín G.; Pereira, Vitor P.; Marinho, Thiago S.; Teixeira, Vicente P.A.; Ferraz, Mara L.F.; Soares, Marina B.; Schultz, Cesar L.
Abstract: Pseudo–coprolites are inorganic structures often confused with fossil faeces. The absence of some diagnostic features, such as inclusions, coprofabrics, grain adhesion, and defined shape, suffices to disregard these structures as coprolites. Herein we revise the so–called "coprolites" from the Serra da Galga Member of the Marília Formation (Maastrichtian of Bauru Group, Paraná Basin), at "Ponto 1 do Price" locality near the town of Peirópolis (Uberaba municipality, Minas Gerais State, Brazil) and conclude that they are, in fact, pseudo–coprolites related to calcretes. These data also agree with the geological setting of "Ponto 1 do Price", composed mainly of coarse sandstones and conglomerates, in which these pseudo–coprolites were found. In addition, some of these specimens exhibit superficial traces, here described as a new boring ichnospecies, Asthenopodichnium fallax isp. nov., produced by invertebrates in Late Cretaceous fresh–water settings of Brazil. Graphical abstract: Highlights: The calcitic, shapeless "coprolites" of the Marília Formation are redescribed as calcrete clasts. Invertebrate borings are described and a new ichnospecies ( Asthenopodichnium fallax ) is erected. It is reported the first occurrence of Asthenopodichnium in hardgrounds.